[Zn(OOCH)2(4, 4′-bipyridine)]n: A metal-organic-framework (MOF) with x-ray-induced photochromic behaviour at room temperature. (April 2019) - Jin, Ai-Ping; Chen, Zi-Wei; Wang, Ming-Sheng; Guo, Guo-Cong
Abstract: Materials that may show photochromism under X-rays have higher spatial resolution for visual low-energy X-rays detection over the commercial instruments and greater X-ray sensitivity than silver salt-based radiographic films. In this work, we discovered that the known MOF, [Zn(OOCH)2 (Bpy)] n (Bpy = 4, 4′-bipyridine), showed rare photochromic behaviour upon irradiation of hard and soft X-rays at room temperature. Graphical abstract: Rare X-ray-induced photochromism at room temperature, with potential application for X-ray detection, was observed for a known MOF. Highlights: Rare X-ray-induced photochromism at room temperature was observed for a known MOF built by non-photochromic ligands. The mechanism of the X-ray-induced photochromic has been studied. The MOF shows a potential application on X-ray detection.